2016
DOI: 10.1039/c6ra14835b
|View full text |Cite
|
Sign up to set email alerts
|

A FRET-based fluorescent approach for labetalol sensing using calix[6]arene functionalized MnO2@graphene as a receptor

Abstract: A turn-on fluorescent sensing platform for labetalol has been developed based on competitive host–guest interaction between p-sulfonated calix[6]arene (SCX6) and target molecule by using SCX6 functionalized MnO2@reduced graphene oxide as a receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Based on competitive host-guest recognition, CA-4@RGO and CA-5@RGO were used as a fluorescent probe for the sensitive and selective detection of tadalafil and aconitine, respectively. Later in 2016, Ye et al (2016) also reported a facile competitive fluorescent sensing platform by using CA-4-MnO 2 @RGO composite as a receptor. The ternary nanocomposites CA-4-MnO 2 @RGO simultaneously possess the excellent quenching performance of MnO 2 @RGO and the high supramolecular recognition capability of CA-4, which was used as a fluorescent probe for the sensitive and selective detection of labetalol in human serum samples.…”
Section: Functionalization Of Graphene With Calix[n]arenesmentioning
confidence: 99%
“…Based on competitive host-guest recognition, CA-4@RGO and CA-5@RGO were used as a fluorescent probe for the sensitive and selective detection of tadalafil and aconitine, respectively. Later in 2016, Ye et al (2016) also reported a facile competitive fluorescent sensing platform by using CA-4-MnO 2 @RGO composite as a receptor. The ternary nanocomposites CA-4-MnO 2 @RGO simultaneously possess the excellent quenching performance of MnO 2 @RGO and the high supramolecular recognition capability of CA-4, which was used as a fluorescent probe for the sensitive and selective detection of labetalol in human serum samples.…”
Section: Functionalization Of Graphene With Calix[n]arenesmentioning
confidence: 99%
“…In the following part of this review, we’ll provide a comprehensive prospectus on the recent development of FRET materials based on host-guest chemistry. Supreme applications for the novel FRET materials supported by host-guest building blocks will be discussed, including protein assembly [ 38 , 39 ], enzyme assays [ 56 ], diagnosis [ 57 ], drug delivery monitoring [ 41 , 42 ], sensing [ 43 , 44 , 45 , 46 , 47 ], photosynthesis mimicking [ 48 , 49 ], and chemical encryption materials [ 58 , 59 ] achieved by the collaboration.…”
Section: Basic Studies For Fret Systems Based On Host-guest Chemismentioning
confidence: 99%
“…Subsequently, Xie et al published their work on the development of the FRET sensor for labetalol (heart-rate reducer) following the same principle as above. [ 47 ] p -Sulfonated calix[6]arene (SCX6) was selected to be the host molecule and Rhodamine 6G (R6G) as the competitive agent ( Figure 5 b). However, they made a remarkable difference by doping MnO 2 on the reduced graphene oxide monosheet to yield MnO 2 @RGO—a fluorescence quencher with higher efficiency.…”
Section: Applications Of Fret Systems Based On Host-guest Chemistrmentioning
confidence: 99%
See 2 more Smart Citations